Lingkungan Rawa Pening Sebagai Sumber Belajar Geografi SMA di Kabupaten Semarang - Fadilah, Nur; Santoso, Apik Budi; Sriyanto, Sriyanto (Edu Geography, 2018)
Research in the background by teachers who have not utilized environment Rawa Pening that has great potential to become a source of learning geography High School in Semarang distric in an outdoor study. Research purposes are: (1) To identify environment Rawa Pening that can be utilized as learning source of geography in High School, (2) To know the relevance of environment Rawa Pening with basic geography competence of High School Semarang distric, (3) To know reason teacher who have not utilized of environment Rawa Pening as a source of learning gegraphy High School. This research is a quantitative research by using Deskriptif Persentase analysis. The population in this research is all high school geography teacher of Semarang distric. For sampling with purposive sampling technique. From the results of the research obtained information 38,46% of respondent said the environment Rawa Pening is excellent used as a source of learning geography High School Semarang distric good physical, social and artificial aspect. Relevance between the environment Rawa Pening with basic competence of geography High School curriculum 2013 69,23% of respondents say good. 46,15% respondents have not utilized environment Rawa Pening as a source of geography learning indoor study only. Main reason teacher have not utilized as outdoor study because limited time and expensive cost. Penelitian dilatarbelakangi oleh guru yang belum memanfaatkan lingkungan Rawa Pening yang memiliki potensi besar untuk menjadi sumber belajar geografi SMA di Kabupaten Semarang secara outdoor study. Tujuan penelitian ini: (1) mengidentifikasi lingkungan Rawa Pening yang dapat dimanfaatkan sebagai sumber belajar geografi di SMA, (2) mengetahui relevansi lingkungan Rawa Pening dengan kompetensi dasar geografi SMA di Kabupaten Semarang, (3) mengetahui alasan guru belum memanfaatkan lingkungan Rawa Pening sebagai sumber belajar geografi. Penelitian ini merupakan penelitian kuantitatif dengan menggunakan analisis Deskriptif Persentase. Populasi dalam penelitian ini adalah seluruh guru geografi SMA di Kabupaten Semarang. Pengambilan sampel dengan teknik purposive sampling, dari hasil penelitian diperoleh keterangan 38,46% responden mengatakan lingkungan Rawa Pening sangat baik digunakan sebagai sumber belajar geografi baik aspek fisik, sosial dan buatan. Relevansi antara lingkungan Rawa Pening dengan kompetensi dasar geografi SMA kurikulum 2013 69,23% responden mengatakan baik. 46,15% responden memanfaatkan lingkungan Rawa Pening sebagai sumber belajar geografi hanya indoor study. Alasan utama guru belum memanfaatkan secara outdoor study karena waktu yang terbatas dan biaya yang mahal.